Enhanced electrolyte and electrode for li-o2 battery discharge - Wijaya, Olivia (2016)
High energy storage demand from electrical vehicle (target set by U.S Advanced Battery Consortium: 350 Whkg-1), has sparked the interest to investigate battery system beyond the Li-ion batteries, which is projected to reach their highest energy density of only 250 Whkg-1. Li-O2 battery is one of such system that promises high theoretical energy density of 3460 – 3860 Whkg-1, ten times higher compared to the theoretical energy density of currently available Li-ion battery, LiCoO2 387 Whkg-1.